Music meets surgery: two sides to the art of “healing” - Moris, Demetrios N.; Linos, Dimitrios (Surgical endoscopy, 2013)
Background The effect of music in the operating room is not fully understood. Through a systematic review the authors aim to give a conceptual presentation of the effect that music has on the pre- and postoperative course of surgical patients and on the effectiveness of the surgical work performed by both physicians and staff. Methods The search was conducted both on the basis of the Medical Subject Headings (MeSH) tree and as a text search using the Medline database (1946 to December 2011). The main search heading was “music in operating room” with the accessory keyword “surgery.” The selection criteria specified the English language and the availability of abstracts or full-text articles. From 85 articles listed with the corresponding search, 28 were relevant and enrolled for the review. Results Patients exhibit lower anxiety levels before and during surgery when hearing music and a significant reduction in analgesia and sedation requirements has been observed. Music was found to reduce the heart rate, blood pressure, and muscle effort of surgeons while at the same time increasing the accuracy of surgical tasks. Surgeons who played a musical instrument were found to perform surgical tasks faster. On the other hand, anesthesiologists report that music is associated with difficulties communicating and offering a stable level of sedation. The most appropriate music in the operating room seems to be the classical type. Conclusions Music in the operating room can have beneficial effects on patients by decreasing stress, anxiety, and the demand for analgesic and anesthetic drugs. For the surgical staff, music is considered to be distracting. For the surgeon, music can increase the speed and accuracy of task performance.